2013
DOI: 10.1097/bpo.0b013e318279c61d
|View full text |Cite
|
Sign up to set email alerts
|

The Bangladesh Clubfoot Project

Abstract: Level 2-therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 8 publications
3
26
0
Order By: Relevance
“…As previously reported [1, 3, 17, 32], we found that children beginning treatment at a younger age, had better outcomes overall, and were less likely to require additional treatment following the standard Ponseti treatment course. Parents were understandably displeased with any further treatment requirements, and less functional outcomes for their children (as occurred in 14 cases reviewed after 4 years).…”
Section: Discussionsupporting
confidence: 87%
“…As previously reported [1, 3, 17, 32], we found that children beginning treatment at a younger age, had better outcomes overall, and were less likely to require additional treatment following the standard Ponseti treatment course. Parents were understandably displeased with any further treatment requirements, and less functional outcomes for their children (as occurred in 14 cases reviewed after 4 years).…”
Section: Discussionsupporting
confidence: 87%
“…There are several examples of successful and sustainable implementations of clubfoot programs in low-and middle income programs [5,8,22]. This could be a great solution in Indonesia, because at present there is no national program giving access to clubfoot care for the whole population in need.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was found in Cape Town and Bali and Sumatra and confirms similar findings in Asia [18,20], Africa [15] and the Americas [14,21], where physical accessibility is described as a barrier for the Ponseti treatment as well. Specialized clubfoot clinics in rural areas are previously proven as a solution for overcoming this barrier [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…Methods have been developed for extending the treatment to developing regions, which often have few surgical resources. The first 5000 feet treated as part of a Ponseti program in Bangladesh were recently reported 10 . Each site was required to keep details regarding clubfoot severity, procedures, results, and complications.…”
Section: Foot and Anklementioning
confidence: 99%